KEJADIAN DROP OUT ALAT KONTRASEPSI HORMONAL PADA WANITA PASANGAN USIA SUBUR DI WILAYAH KECAMATAN SEMARANG TIMUR KOTA SEMARANG TAHUN 2018 - Theresia Christiarini Kuntalawati; Cahya Tri Purnami; R. Djoko Nugroho; Farid Agushybana (Jurnal Kesehatan Masyarakat (Undip), 2020)
The contraceptive drop out rate in East Semarang District is the highest among other district in Semarang City. This study aims to describe the characteristic of women of childbearing age couple in the event of contraceptive drop out. This study uses explanatory research methods and cross sectional study design with a population of 1065 people who stop using contraception in 2018. Study sample taken by simple random sampling of 63 women of childbearing age couples. The results that contraceptive drop out occurs most frequently in women of childbearing age who are of an unhealthy reproductive age (50,8%), advanced education level (77,8%), not working (81,0%), have a good level of knowledge (63,0%), and low parity (77,8%).